2016
DOI: 10.1016/j.ijsu.2016.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of harmonic focus scalpel in seroma prevention after axillary clearance

Abstract: In our hands, HF use was not superior to CD in limiting seroma formation in ALND for breast cancer. Increased seroma formation in surgeries >2.5 h in duration is commensurate with surgeries involving mastectomy and ALND (>2.5 h in our study), which entails greater and sustained tissue and lymphovascular trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
2
4
0
2
Order By: Relevance
“…However, this study demonstrated that the rate of postoperative seroma was comparable between the Harmonic scalpel and monopolar electrocautery. In concordance with our findings, Archana et al [ 15 ] and Selvendran et al [ 18 ] reported no significant difference between the Harmonic scalpel and monopolar electrocautery regarding the incidence of post-BC surgery seroma. Similar findings were reported by others [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, this study demonstrated that the rate of postoperative seroma was comparable between the Harmonic scalpel and monopolar electrocautery. In concordance with our findings, Archana et al [ 15 ] and Selvendran et al [ 18 ] reported no significant difference between the Harmonic scalpel and monopolar electrocautery regarding the incidence of post-BC surgery seroma. Similar findings were reported by others [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, in the present study, we demonstrated that the rate of postoperative seroma was comparable between Ultrasonic shear and monopolar electrocautery. In concordance with our ndings, Archana et al (25), and Selvendran et al (27), reported no signi cant difference between Ultrasonic shear and monopolar electrocautery regarding the incidence of post-BC surgery seroma. Similar ndings were reported by other studies(28,29).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, Militello et al [14], Selvendran et al [57] and Manjunath et al [58] showed how the application of HS did not reduce the incidence of seroma after breast surgery. Furthermore, despite the alternative results, various studies underline the high costs for the usage of HS [52,57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, subsequent studies, reported significant reduction in seroma formation [ 51 – 53 ], reduced intra-operative time [ 54 ], reduced intra-operative blood loss [ 55 ] and reduction in drainage output [ 56 ]. On the other hand, Militello et al [ 14 ], Selvendran et al [ 57 ] and Manjunath et al [ 58 ] showed how the application of HS did not reduce the incidence of seroma after breast surgery. Furthermore, despite the alternative results, various studies underline the high costs for the usage of HS [ 52 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%